Effects of extraction solvent system, time and temperature on total phenolic content of henna (Lawsonia inermis) stems - Tan, Mun Chieng; Tan, Chin Ping; Ho, C. W. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Henna plant ( Lawsonia inermis ) is an Indian medicinal plant used in traditional medicine for the treatment of various diseases, besides its popularity as a natural dye to colour hand and hair. Research in the recent past has accumulated enormous evidence revealing henna plant to be an excellent source of antioxidants such as total phenolics. In this study, the extraction of total phenolics from henna stems was evaluated using the Folin-Ciocalteu assay. A set of single factor experiments was carried out for identifying the optimum condition of each independent variable affecting total phenolic content (TPC) extraction efficiency of henna stems, namely the solvent type, solvent concentration (v/v, %), extraction time (min) and extraction temperature ( o C). Generally, high extraction yield was obtained using aqueous acetone (about 40%) as solvent and the extraction yield could further be increased using a prolonged time of 270 min and a higher incubation temperature of 55°C. Under these optimized conditions, the experimental maximum yield of TPC of 5554.15 ± 73.04 mg GAE/100 g DW was obtained.